Towards a New Strategy for Qur’anic Terms Translation - LACHGAR, Adil (International Journal of Language and Literary Studies, 2023)
The translation of Qur’anic terminology is a complex process. Translation of the Holy Qur’an into English is meant for communication of the Qur’anic Message to the whole world. Therefore, the role of the translator of Qur’anic terms is to convey the true meanings of these terms. Any misinterpretation of the Qur’anic terms will result in a huge loss of their meanings. Therefore, this study aims at investigating the useful of conveyance strategy in translating some terms that are related to “al?ibaadaat” (Islamic observances), “al?aqiida” (belief) and “almu?aamalaat” (interpersonal relations). For the sake of this study, this is a qualitative, comparative and analytical study. The results showed that the task of the translator as a mediator between languages, cultures, and between people is not that an easy task. The use of conveyance can help the translator to overcome the challenges that arise during the translation process. What is more, the ultimate goal of translating the meanings of the Holy Qur’an is to make sure that Allah’s Message is transmitted and understood by people. Hence, conveyance strategy can help the translator delivers the message to the target reader. The strategy of conveyance is of great importance in translating Qur’anic terms since it aims at communication.